Kajian Yuridis Hambatan Penanggulangan Kasus Pornografi di Polres Boalemo dan Pendekatan Solutif untuk Penguatan Perlindungan Korban - Latili, Nurlin; Rusdiyanto U. Puluhulawa, Mohamad; Towadi, Mellisa (PT. Meja Ilmiah Publikasi, 2025)
This study aims to analyze the legal and non-legal obstacles in handling pornography cases at the Boalemo Police Headquarters and formulate a solution to strengthen victim protection. The main questions answered are how legal, technical, and social obstacles affect the effectiveness of handling pornography cases, and what solutions can be implemented to improve victim protection comprehensively. The research method used is empirical juridical with observation techniques, in-depth interviews with investigators, victims, and related parties, as well as documentation of legal documents and relevant literature. The data is analyzed qualitatively by linking the legal and social aspects of the case. The research method used is empirical legal research with techniques of observation, in-depth interviews with investigators, victims, and relevant parties, as well as documentation of legal documents and relevant literature. Data is analyzed qualitatively by linking field findings to victim protection theory and applicable legal provisions. The results of the study indicate that the Boalemo Police have enforced the law against perpetrators of pornography in a procedural manner, maintaining the confidentiality of identities and providing psychological assistance to victims. However, victim protection is still dominated by a repressive approach and is not yet optimal in terms of psychological, social, and economic recovery. The main obstacles found include regulatory disharmony between the Pornography Law and the ITE Law, limited digital forensic facilities, weak inter-agency coordination, low legal and digital literacy among the public, and social stigma towards victims. The findings emphasize the importance of strengthening inter-agency coordination, legal education and digital literacy, as well as developing an integrated victim support system. This study recommends strengthening integrated service units, enhancing the capacity of cyber law human resources, harmonizing technical regulations, and providing preventive education to the public. These findings are expected to serve as a reference for the development of more adaptive and responsive policies and law enforcement practices in protecting victims of digital crimes at both the regional and national levels.